Stroke patients admitted within normal working hours are more likely to achieve process standards and to have better outcomes. Issue 2 (18th August 2015) - Turner, Melanie; Barber, Mark; Dodds, Hazel; Dennis, Martin; Langhorne, Peter; Macleod, Mary-Joan
Abstract : Background: The presence of a 'weekend' effect has been shown across a range of medical conditions, but has not been consistently observed for patients with stroke. Aims: We investigated the impact of admission time on a range of process and outcome measures after stroke. Methods: Using routine data from National Scottish data sets (2005–2013), time of admission was categorised into weekday, weeknight and weekend/public holidays. The main process measures were swallow screen on day of admission (day 0), brain scan (day 0 or 1), aspirin (day 0 or 1), admission to stroke unit (day 0 or 1), and thrombolysis administration. After case-mix adjustment, multivariable logistic regression was used to estimate the OR for mortality and discharge to home/usual place of residence. Results: There were 52 276 index stroke events. Compared to weekday, the adjusted OR (95%CI) for early stroke unit admission was 0.81 (0.77 to 0.85) for weeknight admissions and 0.64 (0.61 to 0.67) for weekend/holiday admissions; early brain scan 1.30 (0.87 to 1.94) and 1.43 (0.95 to 2.18); same day swallow screen 0.86 (0.81 to 0.91) and 0.85 (0.81 to 0.90); thrombolysis 0.85 (0.75 to 0.97) and 0.85 (0.75 to 0.97), respectively. Seven-day mortality, 30-day mortality and 30-day discharge for weekend admission compared to weekday was 1.17 (1.05 to 1.30); 1.08 (1.00 to 1.17); and 0.90 (0.85 to 0.95), respectively. Conclusions: Patients with stroke admitted out of hours and at weekends or public holidays are less likely to be managed according to current guidelines. They experience poorer short-term outcomes than those admitted during normal working hours, after correcting for known independent predictors of outcome and early mortality.